2011
DOI: 10.1177/1045389x11424217
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Testing and Modeling of an MR Squeeze Mount

Abstract: MR fluid squeeze mode investigations at CVeSS have shown that MR fluids show large force capabilities in squeeze mode. It was found that MR fluids in squeeze mode may be used in a wide range of applications such as engine mounts and impact dampers. In these applications, MR fluid is flowing in a dynamic environment due to the transient nature of inputs and system characteristics. The research presented in this article undertakes the problem of dynamic testing and modeling of MR fluid squeeze mounts. Dynamic te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 38 publications
0
32
0
Order By: Relevance
“…As the flow mode and the shear mode, the magnetic chain is broken by shear force and it is broken by squeeze force as the squeeze mode. And the squeeze mode, under the same external excitation, can produce largest response force, showing extensive application potential (Chen et al, 2016b; Mazlan et al, 2007; Sapiński and Gołdasz, 2015; Vieira et al, 2003; Zapoměl et al, 2017; Zhang et al, 2011), and the work range of squeeze mode is smaller than the other modes (Wang et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…As the flow mode and the shear mode, the magnetic chain is broken by shear force and it is broken by squeeze force as the squeeze mode. And the squeeze mode, under the same external excitation, can produce largest response force, showing extensive application potential (Chen et al, 2016b; Mazlan et al, 2007; Sapiński and Gołdasz, 2015; Vieira et al, 2003; Zapoměl et al, 2017; Zhang et al, 2011), and the work range of squeeze mode is smaller than the other modes (Wang et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Mazlan et al (2007Mazlan et al ( , 2008aMazlan et al ( , 2008bMazlan et al ( , 2009Mazlan et al ( , 2011 further revealed the effects of squeeze velocity, squeeze gap, and current intensity. Zhang et al (2011) studied the MRF dynamic behaviors up to 50 Hz. The morphological changes of MRF during the squeeze process were observed and the internal physical state changes of MRF in squeeze mode were explained by Sapin´ski et al (2014) and Ismail et al (2012).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations